A new insight into the rechargeable mechanism of manganese dioxide based symmetric supercapacitors. Issue 14 (26th January 2017) - Chen, Hongyuan; Zeng, Sha; Chen, Minghai; Zhang, Yongyi; Li, Qingwen
Abstract : In symmetric supercapacitors based on MnO2, only MnO2 on the negative electrode serves as the electrochemically active material. MnO2 on the negative electrode dissolves and re-deposites on the positive electrode, thus induces a decrease in specific capacitance. Abstract : Pseudocapacitive symmetric supercapacitors, where both the cathode and the anode have the same pseudocapacitive material, have been widely investigated for developing high-performance supercapacitors. However, being different from electrochemical double-layer (EDL) capacitive electrodes, the charge storage of pseudocapacitive materials relies on reversible redox reactions that change the ion valence status, which is not the case for EDL capacitors (EDLCs). In this research, as a typical inorganic pseudocapacitive material for supercapacitors, a manganese dioxide (MnO2 ) based symmetric supercapacitor was carefully investigated by using a flexible and ultra-light carbon nanotube (CNT) film as the current collector and substrate for MnO2 electrodeposition. The results indicated that the pristine active material on the positive electrode showed no change after cyclic charging/discharging, but only served as a stable counter electrode and reference electrode. The main redox reaction for the energy storage of the supercapacitor occurred on the negative electrode. Furthermore, the dissolved Mn 2+ ions on the negative electrode were deposited onto the positive electrode, which induced an increase in mass of the positive electrode and a decrease in mass of the negative electrode. This research could give new insight into the working mechanism of MnO2 electrodes and other pseudocapacitive materials in symmetric supercapacitors.